2017
DOI: 10.3390/molecules22101660
|View full text |Cite
|
Sign up to set email alerts
|

Selective O-Alkylation of the Crown Conformer of Tetra(4-hydroxyphenyl)calix[4]resorcinarene to the Corresponding Tetraalkyl Ether

Abstract: Reactions of glycidyl methacrylate with the crown and chair conformers of tetra(4-hydroxyphenyl)calix[4]resorcinarene were studied. The reactions were done over epoxide groups present in the ester, which can easily undergo an opening reaction with hydroxyl groups in the macrocyclic system. Initially, epoxidation reactions were carried out with pure conformers, and it was observed that the reaction between tetra(4-hydroxyphenyl)calix[4]resorcinarene fixed in the chair conformation does not occur, while for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
4
17
0
Order By: Relevance
“…According to this analysis, the crown conformer of 4 was the one fixed on the copolymer surface, maintaining the selective character of the process previously observed in solution. 25 In order to determine if the medium influenced the modification of the polymer, the reaction was performed with resorcarene 4 in acidic and basic medium. In both reactions the oxirane rupture is generated by producing diol (2,3-dihydroxypropyl methacrylate) or its isomer (1,3-dihydroxypropyl methacrylate), the latter being a minor product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this analysis, the crown conformer of 4 was the one fixed on the copolymer surface, maintaining the selective character of the process previously observed in solution. 25 In order to determine if the medium influenced the modification of the polymer, the reaction was performed with resorcarene 4 in acidic and basic medium. In both reactions the oxirane rupture is generated by producing diol (2,3-dihydroxypropyl methacrylate) or its isomer (1,3-dihydroxypropyl methacrylate), the latter being a minor product.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the glycidylmethacrylate oxirane opening reaction by using tetra(p-hydroxyphenyl)resorcarene proceeds selectively at the lower rim hydroxyl group without a reaction of the upper rim hydroxyl groups, observing that this trend in solid phase is similar to that observed in solution. 25…”
Section: Introductionmentioning
confidence: 99%
“…Polyhydroxylated platforms such as calixarenes, resorcinarenes, or pyrogalloarenes (Figure 1) are a very interesting class of compounds. They have a remarkable ability to act as receptors for a variety of guest species, depending on their structural properties [23,24,25,26,27], which can be modified by changing the size of the substituents or by adding functional groups as a part of the scaffold [28,29,30,31,32]. Among the described macrocyclic compounds, calixarenes are probably the most promising for application in the area of host–guest recognition of toxicological molecules.…”
Section: Calix[n]arenesmentioning
confidence: 99%
“…Continuing with our studies of the structure of polyhydroxylated platforms [12,33,40,41], we found that the bulky aromatic substituents on the lower rim of polyhydroxylated platforms in cone conformation exhibited a dynamic behavior, which stimulated interest in examining the conformational preferences. For this purpose, in this article, the comparative behavior of Ctetra(phenyl)-resorcin [4]arene (1) and C-tetra(phenyl)pyrogallol [4]arene (2) compounds is studied using 1 H-NMR and 13 C-NMR data and dynamic 1 H-NMR spectra.…”
Section: Synthesis and Separation Of Conformersmentioning
confidence: 55%